(3HOQ GdhGYXjf hPNQ GdYGHOjfs - (3GdcQeGfj, GHf edc, YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG (B, 801 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdeLdS GdChd aj GdEjeGf (B, (3GdeLdS GdKGfj aj cdeI GdJhMjO (B, (3GdeLdS GdKGdK aj GdhVhA (B, (3GdeLdS GdQGHY aj GdBPGf GdeLdS GdNGeS aj GdJcHjQ hGdfjI hGSJbHGd GdbHdI (B, (3GdeLdS GdSGOS aj GdUdGIs
(3BNQgG (B:s
(3dh ChUi HUdHGI YeQg hYeQg eYdhe UM hEf cGf dG jOQj YeQg aGdhUjI HGWdI hdh ChUi HKdK eGdg Edi UdGI YeQg hYdjg Ojf aCjVG hUjI dG jLhR dCf GdhUjI eJCNQI Yf GdOjf JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\59s
(3cTa GdXfhf (B1/231s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs